Surprising heat transfer in new semiconductor under high pressure. (1st March 2023) - Dumé, Isabella
Abstract : The thermal conductivity of materials usually increases when they are subject to very high pressures. But researchers at UCLA have found that the opposite is true for boron arsenide, a newly discovered semiconductor that shows promise in electronics devices.